PEMANFAATAN BAMBU SEBAGAI CELENGAN TRADISIONAL UNTUK KESADARAN MENABUNG ANAK-ANAK DI DESA HILINDRASONIHA - Michael Laia; Citra Sarumaha; Egis Hulu; Elisabeth Gaurifa; Imannuel Duha; Lisda Telaumbanua; Nelson Duha; Nibezokho Duha; Titin Dakhi; Westi Sarumaha; Yudika Daya; Murnihati Sarumaha (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
Saving is a life skill that needs to be instilled from an early age. However, technological advancements and modern lifestyles often lead children to become more consumerist and less inclined to set aside money. Through the Community Service Program (KKN) in Hilindrasoniha Village, a student team from Nias Raya University Group 7 utilized bamboo, a readily available local natural resource, to create traditional piggy banks. This program aimed to examine the use of bamboo as a traditional piggy bank to raise awareness of saving among children in Hilindrasoniha Village. The research was motivated by the low financial literacy of the community, especially children, and the importance of instilling savings habits from an early age. Bamboo piggy banks were chosen as an educational tool because they are environmentally friendly, economical, readily available, and based on local wisdom, appropriate to local conditions. The implementation method included preparation, piggy bank production, implementation of savings habits, and evaluation of program results. The results showed that the children showed high enthusiasm for using bamboo piggy banks, and they began to develop the habit of setting aside some of their money for savings.